Implementation Of A Computer Course Program In Improving The Digital Skill Of Training Participants At LKP Sulthan Computer Bondowoso - Aurelia, Zakinah; Imsiyah, Niswatul; Purnamawati, Frimha (Learning Community : Jurnal Pendidikan Luar Sekolah, 2024)
This research aims to describe the implementation of a computer course program in improving the digital skills of training participants at LKP Sulthan Computer Bondowoso. The technique for determining the location uses a purposive area and the technique for determining informants used is purposive sampling. The type of research used is descriptive research using a qualitative approach. The data collection methods used are observation, interviews and documentation methods. The data analysis techniques used are data collection, data reduction, data presentation and conclusions. The results of this research can be concluded that the places and facilities at the Sulthan Computer LKP include computers, theory rooms and practice rooms, the presentation of the material provided is in accordance with the SKKNI Perpes Number 08 of 2012 curriculum, practice and assignments in the graphic design program, namely designing pamphlets and banners. The problem that often occurs at the Sulthan computer LKP is the difference in the comprehension abilities of training participants. At the end of the course program the instructor reflects on closing the program to review the training participants' achievements. The skills and creativity of trainees can be seen from the way trainees operate computers and communication skills which are often applied during the learning process